PENGARUH TINGKAT INFLASI, TINGKAT SUKU BUNGA BI, DAN NILAI TUKAR USD-IDR TERHADAP PERUBAHAN HARGA SAHAM SEKTOR PERUSAHAAN MANUFAKTUR DI INDONESIA - Stefanus, Adi Cahya; Robiyanto, Robiyanto (International Journal of Social Science and Business, 2020)
The objective of this study is to find out how macroeconomic factors such as exchange rate, BI rate and inflation rate can affect the manufacturing  sector stock price index in IDX from 2011 until 2018. Generalized Autoregressive Conditional Heteroscedasticity (GARCH) is used as the analysis method in this research to find the fittest model. The result, only exchange rate that no significant effect to manufacturing sector stock, price index, Inflation and BI rate have significant effect to manufacturing sector stock price index.